The demonstration of low-temperature (350 °C) grown carbon nano-tubes for the applications of through silicon via in 3D stacking and power-via - Lin, H.-Y.; Basu, Nilabh; Chen, S.-C.; Lee, M.-H.; Liao, M.-H. (Applied physics letters, 2022)
Low temperature Carbon Nano-tubes (CNTs) growth technology is developed in this work with the insert of Al (Aluminum) between Ni (Nickel) and Ti (Titanium) as the reactant. The optimized Al thicknesses are also investigated. CNTs growth at the low temperature below 400 °C is the key factor for the back end of line compatible process integration. In this work, we grow the CNTs by thermal chemical vapor deposition process at 350 and 400 °C. The low ratio of peak ID/IG in Raman spectra and scanning electron microscope images proves the CNTs material quality. On the other hand, the high thermal conductivity (k) value of ∼50 W m − 1 K − 1 is also demonstrated. Both high material quality and k value on our low temperature grown CNTs show promising opportunities for the integration of semiconductor three dimensional packages and power-via related applications.